RESPON PESERTA DIDIK TERHADAP E-MODUL BERBANTUAN SIGIL SOFTWARE ELEMEN 3 FASE E MATA PELAJARAN DASAR-DASAR PEMASARAN DI SMK NEGERI 2 BUDURAN SIDOARJO - Lailiyah, Faridatul; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
The implementation of the independent curriculum poses challenges for teachers in schools, including SMK Negeri 2 Buduran Sidoarjo. Teachers are required to innovate in developing teaching materials as a solution to the limited learning resources available to students. This study aims to describe the students' responses to the use of e-modules assisted by SIGIL software in the three-phase E element of the Basic Marketing subject. The subjects of this study were 32 students from Class X Digital Business 2 at SMK Negeri 2 Buduran Sidoarjo. The study employed a questionnaire as a data collection tool, which was then analyzed descriptively using the percentage formula. The results of this study revealed an average student response obtained through two stages: limited trial and large group trial, with a score of 89.4%, indicating high suitability. Therefore, the e-modules received positive responses and are considered suitable for implementation in the learning process.